Motives and features of cross-platform self-presentation of Russian students - M. I. Krishtal; A. V. Shchekoturov (Цифровая социология)
Social networks increasingly act as a full-fledged tool in the process of expressing one’s identity and self- presentation. The object of this study was the cross-platform self-presentation of Russian students in three different social networks: «VKontakte», «Facebook» and «Instagram». The authors consider cross-platformness in the article refers as the ability to simultaneously construct the desired impression in various Internet platforms, taking into account the specifics of their functionality and audience. The subject of the study is the motives and characteristics of cross-platform self-presentation in these social networks. The research method is in-depth interviews with students of Immanuel Kant Baltic Federal University (Kaliningrad, Russia). The paper carries out narrative analysis in a special software package Atlas.ti. The authors pay particular attention to the motivations for using social networks, as well as the similarities and differences in the pictures and content published on different virtual platforms. The main conclusion of this study is that social media users prefer different forms of self-presentations. The authors found that the nature of self-presentation is related both to the motives for using social networks and their technological capabilities. On Facebook, the prerequisite for the formation of self-presentation is the ability to communicate with a more serious and adult audience. In «VKontakte» – to be part of a community consisting mostly of close friends and peers. In «Instagram» – the visual perception of a person by a person. Along with this, the specificity of self-presentation is also affected by the different functionality of social networks. In particular, «Instagram» provides the most effective opportunities for account users to show events from their lives.